TEACHER ENGAGEMENT IN MODERN EDUCATION: THE ROLE OF SERVANT LEADERSHIP, SELF-EFFICACY, AND WORK VALUES: - - Fitriyani Fitriyani; Didik Notosudjono; Widodo Sunaryo (Journal of Language and Literature Education, 2026)
This study aims to analyze the effects of servant leadership, self-efficacy, and work values on teacher engagement and to compare teacher engagement between Civil Servant Teachers (ASN) in public senior high schools and Permanent Foundation Teachers (GTY) in private senior high schools in Bogor Regency. The study employed a quantitative approach with an ex-post facto comparative causal design involving 255 teachers selected through multistage random area sampling and proportional random sampling. Data were collected using Likert-scale questionnaires and analyzed using descriptive statistics, Independent Sample t-test, simple and multiple linear regression, and SITOREM (Scientific Identification Theory to Conduct Operation Research in Education Management) analysis. The results revealed a significant difference in teacher engagement between ASN and GTY teachers, with ASN teachers demonstrating higher levels of organizational attachment and commitment. Servant leadership, self-efficacy, and work values were found to have positive and significant effects on teacher engagement in both groups. Among ASN teachers, work values emerged as the strongest predictor of engagement, whereas self-efficacy showed the strongest influence among GTY teachers. The SITOREM analysis further identified priority indicators requiring improvement, particularly emotional cues, independence, task challenge, and past performance success. In conclusion, teacher engagement is significantly influenced by leadership, psychological, and value-based factors, and strengthening self-efficacy, positive work values, and supportive servant leadership is essential for enhancing sustainable teacher engagement across different educational contexts.